After war, is faith possible? : an anthology - Studdert Kennedy, Geoffrey Anketell, 1883-1929.; Walters, Kerry S. (Cambridge : Lutterworth, 2008)
""There are no words foul and filthy enough to describe war."" So declared Geoffrey 'Woodbine Willie' Studdert Kennedy (1883-1929), a decorated frontline chaplain whose battlefield experiences in World War I transformed him into the most eloquent defender of Christian pacifism of his generation. Studdert Kennedy was also a tireless champion of the social gospel who wrote a dozen books, scores of articles, hundreds of poems, and preached countless sermons in both the UK and the US promoting economic justice. Studdert Kennedy's writing and preaching influenced an entire generation. William Templ.
This Good Samaritan BusinessWork; If I Had a Million Pounds; It's Hard to Be a Carpenter; Sources; Bibliography; Back Cover.
Paperback.
Includes bibliographical references.
Description based on print version record.
Master record variable field(s) change: 072
Keywords: Theology; World War, 1914-1918 -- Religious aspects; Religious aspects; Theology; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Theology; RELIGION / Christian Theology / General; Electronic books